2021
DOI: 10.1002/jctb.6913
|View full text |Cite
|
Sign up to set email alerts
|

Canola meal‐derived activated biochar treated with NaOH and CO2 as an effective tool for Cd removal

Abstract: BACKGROUND: This research assessed the capacity for Cd 2+ removal from water using canola meal-based adsorbents: canola meal chemically activated with 1 mol L -1 NaOH and pyrolyzed for 1 h at 500 °C (CAC) and the second product obtained with a similar process but with a second pyrolysis at 750 °C in CO 2 flow (CAC-CO 2 ). The materials were characterized by their chemical composition and thermal stability and using Fourier transform infrared spectroscopy, pH at point of zero charge (pH PZC ) and scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…As shown in Fig. 3(a), the curve of canola meal exhibited abundant characteristic peaks at 3430 cm −1 , 2927 cm −1 and 2852 cm −1 , 1744 cm −1 and 1658 cm −1 , 1483 cm −1 and 1389 cm −1 , 1035 cm −1 corresponding to the stretching vibration of OH(NH), CH, CO, CO/H and CO groups 10 . The absorption peaks at 1744 cm −1 ,1658 cm −1 and 1544 cm −1 were attributed to the residual oil and the amide I and II of protein in canola meal, while the absorption peaks at 2927 cm −1 and 2852 cm −1 were assigned to the methyl and methylene groups of glucose unit of cellulose or on side chains of amino acids in protein 1,15 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Fig. 3(a), the curve of canola meal exhibited abundant characteristic peaks at 3430 cm −1 , 2927 cm −1 and 2852 cm −1 , 1744 cm −1 and 1658 cm −1 , 1483 cm −1 and 1389 cm −1 , 1035 cm −1 corresponding to the stretching vibration of OH(NH), CH, CO, CO/H and CO groups 10 . The absorption peaks at 1744 cm −1 ,1658 cm −1 and 1544 cm −1 were attributed to the residual oil and the amide I and II of protein in canola meal, while the absorption peaks at 2927 cm −1 and 2852 cm −1 were assigned to the methyl and methylene groups of glucose unit of cellulose or on side chains of amino acids in protein 1,15 .…”
Section: Resultsmentioning
confidence: 99%
“…Scientists have passionately focused on the research development of porous biochar derived from waste biomass in energy storage and contaminants removal in recent years, owing to their specific surface area and porous structure 6‐8 However, there are few reports about porous carbon derived from canola meals as far as we are concerned. Previous studies have indicated that the adsorption capacity of canola meal‐derived biochar for dyes or heavy metal ions is significantly inferior to that of other biochar materials produced via a high‐temperature alkaline activation methods 9,10 . This is primarily due to the intricate chemical composition of canola meals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum Cr (VI) adsorption capacity of 3.51 mg/g was obtained at initial pH of 2.0 and an adsorbent dose of 0.6 g. The results of their adsorption study showed that the Langmuir model was found to fit better to the Freundlich model and pseudo-second order was found to fit as compared to pseudo-first-order kinetics. Gonçalves et al [42] have studied the adsorption of Pb +2 ions from canola meal using H 2 SO 4 modification. Their study revealed that the removal efficiency of 80% Pb +2 ions was obtained at 140 min contact time.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gonçalves et al reported a stronger surface area, a larger pore volume, and a smaller pore size were obtained in the BC modified by NaOH. [20] During thermal treatment, the chemical activation of sodium hydroxide results in the fragmentation and dissolution of lignin and hemicellulose. The hydroxyl ions are more amorphous and less polymerized than the cellulose component.…”
Section: Introductionmentioning
confidence: 99%